Hubungan Pengetahuan, Masa Kerja dan Sikap terhadap Perilaku Pemilahan Limbah Medis Padat pada Perawat - Yana Efendi; Desy Sulistiyorini; Rofi'atun Zakiah (Jurusan Kesehatan Lingkungan Poltekkes Kemenkes Padang, 2025)
The issue of solid medical waste management in hospitals remains a serious challenge that can endanger environmental health and increase the risk of disease transmission. In several healthcare facilities, including Zahirah General Hospital, improper medical waste segregation practices are still found, such as the mixing of medical and non-medical waste. This condition indicates a weakness in healthcare workers' behavior towards safe and proper waste management. This study aims to examine the relationship between knowledge, years of service, and attitudes toward solid medical waste segregation behavior among nurses at Zahirah General Hospital. This research employed a quantitative method with a cross-sectional design conducted from October to December 2024. Data were collected using questionnaires distributed to nurses at Zahirah General Hospital, then analyzed univariately and bivariately using the Chi-Square test. The results showed no significant relationship between knowledge and segregation behavior (p = 0.412), nor between years of service and behavior (p = 0.200). However, there was a significant relationship between attitude and behavior (p = 0.030; OR = 2.681). These findings indicate that nurses' attitudes play a key role in the effectiveness of medical waste segregation. This study highlights the importance of ongoing education and training programs on medical waste management for all hospital staff to increase awareness, responsibility, and engagement in proper waste segregation practices. These efforts are essential to support a safe and healthy hospital environment.